Detección de vibrios patógenos en bocachico (Ichthyoelephas Humeralis) en los Ríos Mocache y Vinces, Ecuador. - Ortiz Macías, Leonel Teobaldo (2020)
The present investigation aimed to determine the presence of pathogenic bacteria of the genus Vibrio spp. in bocachico (Ichthyoelephas humeralis) in the Mocache and Vinces rivers in the Los Ríos province. The microbiological and molecular experiments were carried out in the microbiology and molecular biology laboratory of the La María campus of the Quevedo State Technical University. The fish were obtained directly from the fishermen, 60 organisms for each river. Morphometric analysis (LT and PT) and biological (IGS, IHS and FC) were performed on the sampled fish, in addition to microbiological isolation and molecular analysis. The results obtained show that the bocachico is one of the species with the highest consumption in areas near the Mocache and Vinces rivers, which was corroborated through a survey where 47 and 43% of the individuals surveyed preferred to consume bocachico. The morphometric analysis indicated that the Mocache river fish have higher values regarding total length (TL) 23.91 ± 3.14 cm total weight (PT) 186.44 ± 81.21 g, as well as the highest values of the biological indices: IHS 7.90 ± 7.70; the IGS of 1.28 ± 0.28 and FC of 0.81 ± 0.51. Microbiologically, the bocachico isolates from both the Vinces and Mocache rivers did not show the existence of V. cholera and V. parahaemolyticus, however, the molecular analysis identified us that these isolated bacteria were Plesiomonas sp. and Shewanella sp. with a genetic identity percentage of 97.32% and 99.79%. Concluding that this research is important in the pathological origin of the bacteria analyzed, which can put human health at risk. Keywords: bacteria, bocachico, PCR, Vibrio spp.